The estimation of the special stamina in elite climbers - Kotchenko, Yu. V. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
Here represented the results of many years of studying the competition activity of highly qualified climbers. One of the key components is reviewed - the special stamina. The degree of the connection with the outcome of completing the route is established: R = 0.78, P << 0,001. Two mathematical models are built, that make it possible to calculate indicator of the special stamina and derive preliminary estimation of the readiness degree of athlete by this competition process component.